المؤسسات الصغيرة والمتوسطة في الجزائر: بين إشكالية التنمية الاقتصادية ومتطلبات النهوض - قوفي, سعاد; عياش, زبير (جامعة الوادي - University of Eloued, 2016)
يشهد الاقتصاد العالمي في الآونة الأخيرة تحولات وتطورات كبيرة ناتجة عن ظاهرة التكتلات السياسية والاقتصادية، بالإضافة إلى مختلف الاندماجات الحاصلة بين المؤسسات الكبيرة في العالم الصناعي مما أدى برجال الأعمال ومقرروا السياسات التنموية إلى دعم النمو لقطاع المؤسسات الصغيرة والمتوسطة (م ص م) في الدول المتقدمة والنامية على السواء فأصبح دعم هذا القطاع توجها اقتصاديا عالميا، خاصة وأن هذا التوجيه يحمل في طياته مضامين إيجابية لجميع الدول وبصورة خاصة النامية منها التي تبحث عن أدوات تنموية جديدة لمواجهة تحديات العولمة. ونحاول من خلال هذه الدراسة أن نجيب على السؤال التالي: ما هي المكانة التي يحتلها نموذج التنمية الاقتصادية القائم على دعم الـ مص م ضمن مختلف نماذج التنمية الحديثة وما هي تحدياتها ومتطلبات النهوض ؟ The global economy has witnessed major changes and developments resulting from the phenomenon of political and economic blocs, as well as the various mergers between large institutions in the industrial world, which led businessmen and development policy makers to support the growth of the SME sector in developed and developing countries The support of this sector has become a global economic trend, especially as this guidance carries positive implications for all countries, especially developing ones, which are looking for new development tools to meet the challenges of globalization. In this study, we try to answer the following question: What is the status of the model of economic development based on supporting the establishment within the various models of modern development and what are its challenges and the requirements of advancement?
Small And Medium Enterprises In Algeria Between The Problematic Of Economic Development And The Requirements Of Advancement
مقال
Keywords: المؤسسات الصغيرة والمتوسطة، التنمية الاقتصادية، التحديات، متطلبات النهوض; mall and medium enterprises, economic development, challenges, promotion requirements.